2020
DOI: 10.1101/2020.07.01.20144204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of the IcanSDM scale to assess primary care clinicians’ ability to adopt shared decision-making

Abstract: Introduction: Implementation of shared decision making (SDM) remains a challenge. To support implementation studies, we sought to develop and validate the IcanSDM scale that assesses clinicians' perceptions of their ability to adopt SDM. Methods: An expert panel reviewed the literature on clinician-reported barriers to SDM adoption, to create an 11-item preliminary scale. A convenience sample of 16 clinicians from Quebec (Canada) completed the IcanSDM and the Belief about Capabilities subscale of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Of all the studies, 69% (36/52) were published between 2019 and 2021 [ 9 , 32 - 68 ]. Furthermore, 58% (30/52) were located in Canada [ 7 , 8 , 10 - 12 , 23 - 25 , 28 , 31 , 35 , 38 - 41 , 44 - 51 , 53 , 54 , 56 , 60 , 63 , 65 , 67 ] and the rest in the United States (n=6), the United Kingdom (n=4), Australia (n=2) [ 30 , 34 ], Iran (n=2) [ 55 , 64 ], Argentina (n=1) [ 52 ], Indonesia (n=1) [ 32 ], Germany (n=1) [ 58 ], Sweden (n=1) [ 21 ], the Netherlands (n=1) [ 59 ], and Burkina Faso (n=1) [ 37 ]. In addition, two multicountry studies were reported: 1 from Brazil-China-France-Japan-Mali [ 68 ] and 1 from Canada-Vietnam [ 19 ] ( Table 1 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of all the studies, 69% (36/52) were published between 2019 and 2021 [ 9 , 32 - 68 ]. Furthermore, 58% (30/52) were located in Canada [ 7 , 8 , 10 - 12 , 23 - 25 , 28 , 31 , 35 , 38 - 41 , 44 - 51 , 53 , 54 , 56 , 60 , 63 , 65 , 67 ] and the rest in the United States (n=6), the United Kingdom (n=4), Australia (n=2) [ 30 , 34 ], Iran (n=2) [ 55 , 64 ], Argentina (n=1) [ 52 ], Indonesia (n=1) [ 32 ], Germany (n=1) [ 58 ], Sweden (n=1) [ 21 ], the Netherlands (n=1) [ 59 ], and Burkina Faso (n=1) [ 37 ]. In addition, two multicountry studies were reported: 1 from Brazil-China-France-Japan-Mali [ 68 ] and 1 from Canada-Vietnam [ 19 ] ( Table 1 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…( Table 2 ). In most studies, participants in CPD activities consisted of interprofessional groups (30/52, 60%) [ 7 , 9 - 11 , 19 , 21 , 27 , 28 , 31 , 35 , 37 , 41 , 43 , 44 , 46 , 47 , 50 , 51 , 53 , 55 - 61 , 63 , 64 , 66 - 68 ]. Professions included nurses (5/52, 10%) [ 26 , 29 , 30 , 48 , 54 ], physicians (4/52, 8%) [ 38 , 39 , 49 , 52 ], social workers or other health professionals, namely occupational therapists, physiotherapists, dietitians, behavioral counselors, nutritionists, health researchers (4/52, 8%) [ 23 - 25 , 34 , 36 ], specialist physicians (3/52, 6%) [ 32 , 40 , 65 ], and pharmacists (2/52, 4%) [ 22 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations